Oxydifluoromethylation of Alkenes by Photoredox Catalysis: Simple Synthesis of CF(2)H‐Containing Alcohols - Arai, Yusuke (Chemistry, 2015)
We have developed a novel and simple protocol for the direct incorporation of a difluoromethyl (CF(2)H) group into alkenes by visible‐light‐driven photoredox catalysis. The use of fac‐[Ir(ppy)(3)] (ppy=2‐pyridylphenyl) photocatalyst and shelf‐stable Hu's reagent, N‐tosyl‐S‐difluoromethyl‐S‐phenylsulfoximine, as a CF(2)H source is the key to success. The well‐designed photoredox system achieves synthesis of not only β‐CF(2)H‐substituted alcohols but also ethers and an ester from alkenes through solvolytic processes. The present method allows a single‐step and regioselective formation of C(sp(3))–CF(2)H and C(sp(3))−O bonds from C=C moiety in alkenes, such as hydroxydifluoromethylation, regardless of terminal or internal alkenes. Moreover, this methodology tolerates a variety of functional groups.